An innovative strategy for efficient and economical arsenic removal in hydrometallurgical waste sulfuric acid by co-treatment with Fe–As coprecipitation residue via scorodite formation. (15th November 2022) - Ma, Xu; Su, Rui; Zhu, Xiayu; Zhao, Zhixi; Zeng, Xiangfeng; Wang, Shaofeng; Jia, Yongfeng
Abstract: Hydrometallurgical iron-arsenic (Fe–As) coprecipitation residue (FACR), a massive industrial solid waste, is a potentially cheapest Fe(III) source for the removal and fixation of As in waste sulfuric acid (WSA) as stable scorodite. This study innovatively proposed a method by controlling a low supersaturation degree of ferric arsenate in WSA via stepwise addition and slow dissolution of FACR, ensuring continuous ferric arsenate precipitation and scorodite crystallization. The results showed that As removal efficiency in WSA reached 99.92%. The decrease in the weight of solid waste was up to 37.1%. X-ray diffraction and infrared spectroscopy results indicated that scorodite is the principal crystalline As mineral in the products. The solid products displayed excellent stability with the TCLP concentrations of leached As and divalent metals (Cu II, Pb II, Zn II, and Cd II ) far below the US-EPA regulatory limits. Scanning/Transmission electron microscopy and X-ray photoelectron spectroscopy results revealed that such high TCLP stability could be ascribed to the adsorption of As and trace divalent metals on the raw/secondary Fe-(oxy)hydroxide minerals, such as FeO(OH), goethite, and ferrihydrite. This work provides an economical and efficient method for simultaneous treatment of WSA and FACR, which can support the sustainable development of the hydrometallurgical industry. Graphical abstract: Image 1 Highlights: First attempt in using FACR as an iron source for WSA treatment. Removal efficiency of As from waste sulfuric acid reaches up to 99.92%. Weight loss ratio of solid waste before and after treatment reaches up to 56.8%. TCLP concentrations of As and valuable metals are below the EPA regulatory limits. Scorodite and Fe-(oxy)hydroxide occurs in products are responsible for As fixation.